A gender gap in gender gaps: social norms and housework reporting - Martin Acht; Mara Rebaudo (Empirical Economics, 2025)
Gender differences in the amount of housework performed and the role of social norms in explaining these persistent gaps have received increasing attention from both policymakers and researchers in recent years. However, norms may not only affect the actual division of housework but also potentially influence the reporting behavior in surveys. We study how retrospective responses about time-use in face-to-face interviews are influenced by the gender of the interviewer. Our findings show that women tend to report significantly more hours of housework when interviewed by a woman rather than by a man. This effect is not observable for male respondents, resulting in an interviewer gender gap in the housework gender gap. Exploring the effect in relation to several norm-related characteristics indicates that social norms play an important role in the reporting of housework hours. Therefore, gender gap estimates based on face-to-face interviews should be interpreted with great caution.
Keywords: D13; J16; D90; 330; Gender; Gender gap; Doing gender; Social norms; Interviewer effects